Comparative analysis of cognitive metaphors in English and Uzbek educational discourse - Akoburxanova, Gulchexra (The Lingua Spectrum, 2026)
This article presents a comprehensive comparative analysis of cognitive metaphors alongside semantic shifts and lexical evolution in English and Uzbek educational discourse. The study is grounded in conceptual metaphor theory developed by George Lakoff and Mark Johnson, as well as contemporary approaches in corpus linguistics and linguistic adaptation. It explores universal metaphorical models such as learning as a journey and mind as a container, while placing particular emphasis on two dominant conceptual frameworks: “Investment” and “Enlightenment”. In addition, the research examines how educational terminology evolves under the influence of technological advancement, globalization, and cross-linguistic borrowing, drawing on data from modern linguistic corpora, including COCA. The findings reveal that English educational discourse tends to be pragmatic, goal-oriented, and economically framed, often reflecting the “investment” model, whereas Uzbek discourse demonstrates a stronger orientation toward spiritual, moral, and culturally embedded values associated with the “enlightenment” model. Furthermore, the study shows that while high-frequency lexical units remain relatively stable across both languages, the integration of loanwords and semantic adaptation follows systematic functional and contextual patterns shaped by digital environments. Overall, the research highlights the interaction between universal cognitive mechanisms and culturally specific linguistic realizations, offering a deeper understanding of how metaphor and lexical change jointly shape educational discourse in a cross-cultural perspective.